2023
DOI: 10.1038/s41598-023-30615-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of a disease-resistant genotype of Acropora cervicornis are resistant to acute, but not chronic, nutrient enrichment

Abstract: Chronically high levels of inorganic nutrients have been documented in Florida’s coral reefs and are linked to increased prevalence and severity of coral bleaching and disease. Naturally disease-resistant genotypes of the staghorn coral Acropora cervicornis are rare, and it is unknown whether prolonged exposure to acute or chronic high nutrient levels will reduce the disease tolerance of these genotypes. Recently, the relative abundance of the bacterial genus Aquarickettsia was identified as a significant indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…To test the impacts of nutrient enrichment on A. cervicornis health and microbiome community function, a six-week tank experiment was conducted as previously described (24,27) at the Mote Marine Laboratory International Center for Coral Reef Research & Restoration (24°39'41.9"N, 81°27'15.5"W) in Summerland Key, Florida from April to June 2019. The experiment was conducted in 4.7 L flow-through, temperature-controlled aquaria with natural locally-sourced sea water from the Atlantic side of the Keys.…”
Section: Experimental Design and Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the impacts of nutrient enrichment on A. cervicornis health and microbiome community function, a six-week tank experiment was conducted as previously described (24,27) at the Mote Marine Laboratory International Center for Coral Reef Research & Restoration (24°39'41.9"N, 81°27'15.5"W) in Summerland Key, Florida from April to June 2019. The experiment was conducted in 4.7 L flow-through, temperature-controlled aquaria with natural locally-sourced sea water from the Atlantic side of the Keys.…”
Section: Experimental Design and Sample Collectionmentioning
confidence: 99%
“…A. rohweri specific marker gene) revealed that 'Ca.' A. rohweri responded positively to nutrient enrichment in both host genotypes, however it remained at low relative abundances in the disease-resistant genotype, ML-7 (<0.5% of the total bacterial community) (24). In the disease-susceptible genotype, M-50, 'Ca.'…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations